Building transformative change in Africa’s smallholder food systems: Contributions from climate-smart agriculture and agroecology - Shilomboleni, Helena; Radeny, Maren A.O.; Demissie, Teferi Dejene; Osumba, Joab J.L.; Recha, John W.M.; Solomon, Dawit (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Transforming food systems under a changing climate entails amplifying solutions that build sustainability along multiple interconnected principles—i.e., diversity, resilience, equity, economic viability, health and renewability. Two different approaches are engaged in this transformational work in Africa: climate-smart agriculture (promotes participatory multi-stakeholder collaborations and climate-informed sustainable agriculture innovations) and agroecology (prioritizes co-created diversified livelihood strategies). Together, their contributions highlight the urgency of reconfigurations that balance technology transfer with realigning human values to support inclusive processes and principles of transformation. Taking to scale this critical work will require significant support: donors and policy makers can help by diversifying their investments to create a balance between projects focused on technological solutions and those implementing more agroecological components. Agricultural research for development organizations can help to build the evidence base for agroecology and climate-smart agriculture based on data metrics associated with yields, income, and socioeconomic performance, and on the significance of their holistic approaches to tackling climate change adaptation and mitigation by ensuring strong, resilient social foundations.